Hydrothermal Pretreatment of Hardwood Chips Prior to Alkaline Pulping and D0(EP)D1 Bleaching - Congcong Chi; Mi Liu; Hasan Jameel; Sufeng Zhang; Zeng Zhang (BioResources, 2014)
In this study, mixed southern hardwood was pretreated via a hydrothermal process at 160 °C for 1 h. Alkaline pulping was then conducted on both the pretreated and original chips to prepare pulp with Kappa 17 and 30. For the Kappa 30 pulps, oxygen delignification was further carried out to render Kappa 17. After pulping, the different pulps with similar Kappa 17 were bleached by the D0(EP)D1 sequence. Pulping results show that the pretreated chips are easier to cook and necessitate less alkaline charge to achieve a similar Kappa without decreasing the pulp viscosity. Under similar bleaching conditions, hydrothermal pretreatment leads to pulps with a higher brightness, viscosity, and paper sheet opacity and scattering coefficient, while also lowering the burst and tensile strength. Furthermore, the pulp fiber length, fiber width, and percentage of fines decreases, yet the coarseness, curl index, and kink index increase. However, the paper properties of bleached pulps are not improved significantly when subjected to modified continuous cooking (MCC) pulping or oxygen delignification.